2019
DOI: 10.15288/jsad.2019.80.331
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Heavy Episodic and High-Intensity Drinking: Daily-Level Associations With Mood, Context, and Negative Consequences

Abstract: Underestimating how much one will drink has been associated with greater alcohol-related consequences. Elevated mood or drinking context may relate to drinking more than planned (or intended) among college students. The aims of the current study were to test (a) whether positive and negative mood and contextual factors on a given day were associated with the likelihood of unplanned heavy drinking (defined as unplanned heavy episodic or high-intensity drinking), and (b) whether days with unplanned heavy drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 56 publications
7
68
5
Order By: Relevance
“…consuming five or more drinks in a row) in the previous 2 weeks (Schulenberg, et al, 2019). Heavy alcohol consumption among college students has been consistently linked to adverse outcomes such as academic difficulties, injuries, and death (Fairlie et al, 2019; Hingson et al, 2017; Patrick et al, 2016). Alcohol consumption is also associated with numerous sexual risks in this population, including sexual assault victimization and perpetration (Abbey, 2011; Brown & Vanable, 2007; Cooper, 2002; Crane et al, 2016; Davis et al, 2014; Mohler-Kuo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…consuming five or more drinks in a row) in the previous 2 weeks (Schulenberg, et al, 2019). Heavy alcohol consumption among college students has been consistently linked to adverse outcomes such as academic difficulties, injuries, and death (Fairlie et al, 2019; Hingson et al, 2017; Patrick et al, 2016). Alcohol consumption is also associated with numerous sexual risks in this population, including sexual assault victimization and perpetration (Abbey, 2011; Brown & Vanable, 2007; Cooper, 2002; Crane et al, 2016; Davis et al, 2014; Mohler-Kuo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that positive, but not negative, affect is associated with HED at the daily level in college students (Howard et al, 2015). Fairlie et al (2019) examined whether positive and negative affect and contextual features were associated with the likelihood of unplanned heavy drinking (i.e., crossing either the HED or HID threshold when it was not planned). They found that, on average, participants with higher average positive affect across days had lower odds of unplanned heavy drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Results from Lauher et al (2020) and Fairlie et al (2019) suggest that current conceptualizations of unplanned drinking as a negative event are not supported. It is worth noting that participants who plan to heavily consume alcohol (i.e., more than 5+ drinks as seen in binge drinking) may be at more risk than originally thought.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…This study also used a daily diary design but focused on daily-level factors (i.e., mood, context) that influenced unplanned drinking. Fairlie et al (2019) found that a third of participants' drinking during the study were heavy-unplanned drinking days. They also found that individuals with positive moods across the 10-day period were less likely to engage in heavy unplanned drinking.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
See 1 more Smart Citation